Ecological impacting factors of power objects on environment - Nechaieva T.P.; Shulzhenko S.V.; Sas D.P.; Parasyuk M.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
The classification of the main impacting factors of power objects on environment: atmosphere, water and land resources was considered and proposed in the article. The features of ecological impacts of traditional and nonconventional power sources on environment were defined.